2015
DOI: 10.1590/2359-3997000000117
|View full text |Cite
|
Sign up to set email alerts
|

The influence of glycemic control on the oral health of children and adolescents with diabetes mellitus type 1

Abstract: Objective: To evaluate the influence of disease control, expressed by the mean values of glycated hemoglobin (HbA1c), in the oral health of children and adolescents with diabetes mellitus type 1 (T1DM). Subjects and methods: A cross sectional study involving 87 children and adolescents (59 girls), 10 ± 2.6 years old. The participants were divided into three groups: HbA1c ≤ 8%, 8% < HbA1c ≤ 10% and HbA1c > 10%. The duration of the disease, age and average HbA1c were obtained from their medical records. Oral hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
35
2
12

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 22 publications
2
35
2
12
Order By: Relevance
“…The results of Miko et al (25) also showed that the mean number of decayed teeth in well-controlled T1DM adolescents is lower, but the number of filled teeth is higher than in patients with poorer glycemic control. Carneiro et al (27) demonstrated that the DMFT score was higher in individuals with higher HbA1c values and that more caries-free individuals were found in the group with lower HbA1c. In the study of Sudikiene et al (28), well to moderately controlled diabetics had fewer decayed surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…The results of Miko et al (25) also showed that the mean number of decayed teeth in well-controlled T1DM adolescents is lower, but the number of filled teeth is higher than in patients with poorer glycemic control. Carneiro et al (27) demonstrated that the DMFT score was higher in individuals with higher HbA1c values and that more caries-free individuals were found in the group with lower HbA1c. In the study of Sudikiene et al (28), well to moderately controlled diabetics had fewer decayed surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…Al-Khabbaz, et al 1 (2013) observed that, in children with type 1 diabetes, periodontitis was significantly associated with longer duration of diabetes and older age at diagnosis of diabetes. Studies have demonstrated that poor metabolic control, including high levels of fasting glucose and glycosylated hemoglobin are important factors that could increase the susceptibility to periodontal disease, as well as other systemic complications of diabetes mellitus 3,22 .…”
Section: Discussionmentioning
confidence: 99%
“…CPI (Community Periodontal Index) evaluates three periodontal indicators: bleeding gums, periodontal calculus and periodontal pockets. The CPI was coded by as: 0 = healthy; 1 = bleeding; 2 = calculus; 3 = pocket 4-5 mm; 4 = pocket >6mm; X = sextant excluded; 9 – not registered (8, 9). Participants were also divided into four groups according to their age, as follows: a) Age 6 years (n=10); b) Age 7–12 years (n=17); c) Age 13-18 years (n=30) and d) Age 19-45 years (n=33).…”
Section: Methodsmentioning
confidence: 99%